2020
DOI: 10.1021/acscentsci.0c00813
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Vacuolar Uptake of Fluorescently Labeled Antifungal Drug Caspofungin Predicts Echinocandin Resistance in Pathogenic Yeast

Abstract: Echinocandins are the newest class of antifungal drugs in clinical use. These agents inhibit β-glucan synthase, which catalyzes the synthesis of β-glucan, an essential component of the fungal cell wall, and have a high clinical efficacy and low toxicity. Echinocandin resistance is largely due to mutations in the gene encoding β-glucan synthase, but the mode of action is not fully understood. We developed fluorescent probes based on caspofungin, the first clinically approved echinocandin, and studied their cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 72 publications
(131 reference statements)
1
25
0
Order By: Relevance
“…We tested FCSP and observed that in A. fumigatus the fluorescent drug initially accumulates in the interface cell wall / cell membrane but it is progressively internalized into vacuoles most likely by endocytosis, since possible small endocytic vesicles are observed. Jaber et al (2020) have demonstrated that this FCSP also accumulates in Candida albicans vacuoles and cellular uptake was energy dependent and reduced by endocytosis inhibitors. We propose that FCSP vacuolar trafficking is an attempt of both C. albicans and A. fumigatus to remove the caspofungin-Fks1 (β-1,3-glucan synthase) complexes from the cell membrane by membrane turnover via endocytosis contributing to explain the previous observation that CSP induces A.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We tested FCSP and observed that in A. fumigatus the fluorescent drug initially accumulates in the interface cell wall / cell membrane but it is progressively internalized into vacuoles most likely by endocytosis, since possible small endocytic vesicles are observed. Jaber et al (2020) have demonstrated that this FCSP also accumulates in Candida albicans vacuoles and cellular uptake was energy dependent and reduced by endocytosis inhibitors. We propose that FCSP vacuolar trafficking is an attempt of both C. albicans and A. fumigatus to remove the caspofungin-Fks1 (β-1,3-glucan synthase) complexes from the cell membrane by membrane turnover via endocytosis contributing to explain the previous observation that CSP induces A.…”
Section: Discussionmentioning
confidence: 95%
“…Conidia of each specific strain were grown on coverslips in 4 ml of minimal medium at 30°C. After 16h of incubation, the coverslips with adherent germlings were treated with 0.125µg/mL of a functional fluorescently labeled probe of caspofungin (FCSP) for 5, 15 and 30 min (Jaber et al, 2020). Staining of vacuoles was performed by the addition of 10 µM CellTracker Blue CMAC dye for 10 min at 30°C.…”
Section: Microscopymentioning
confidence: 99%
“…CSF probes were prepared by selective conjugation of the propargyl group to the phenol of the 3 S ,4 S -dihydroxy- l -homotyrosine amino acid of CSF to afford the alkyne-functionalized CSF derivative 1a , which was then coupled to the azide-functionalized fluorescent dye (TMR or NBD) using a click reaction to form fluorescent CSF probes 1 and 2 ( Scheme 1 A) as we previously reported. 32 For the preparation of fluorescent ANF probes 3 and 4 , ANF was reacted with 3-butynyl alcohol under acidic conditions to generate the corresponding 3-butynyl-hemiaminal ether derivative 2a , which was then coupled to the azide-functionalized fluorescent dye using a click reaction to form fluorescent probes 3 and 4 ( Scheme 1 B). RZF was prepared from ANF through etherification of the hemiaminal group with choline under acidic conditions according to a procedure developed by Cidara Therapeutics, 22 followed by propargylation of its 3 S ,4 S -dihydroxy- l -homotyrosine phenol to form the corresponding functionalized echinocandin 3a ( Scheme 1 C).…”
Section: Resultsmentioning
confidence: 99%
“… 32 On average, the level of uptake of the fluorescently labeled CSF was significantly higher in echinocandin-resistant Candida strains than in echinocandin-susceptible strains. 32 …”
Section: Introductionmentioning
confidence: 91%
“…Revisiting the underexploited resources that nature has to offer thus holds significant untapped potential. The echinocandin class of antifungal agents, first introduced in 2001, serve as a strong example of the potential of natural products as scaffolds for drug development [7,8] …”
Section: Introductionmentioning
confidence: 99%